(untitled) (Oratio Directa, 2023)
Television journalists faced major internal and external changes during the COVID-19 pandemic. This qualitative study examines how SCTV and Indosiar journalists adapted their work mechanisms. The findings show that journalists used online reporting for red-zone coverage and interviews that could not be conducted face to face. User-generated content became part of the reporting process when sources recorded their own responses and sent them through WhatsApp. These adaptations supported newsroom continuity while reducing health risks.